Wear of model and integral face milling cutter modelled by artificial intelligence - Kovač, Pavel; Savkovic, Borislav; Rodić, Dragan; Gostimirović, Marin; Mankova, Ildiko (Journal of Production Engineering, 2023)
The paper presents results of experimental study of model single tooth and integral multi tooth milling cutter. During the study research were tool wear on rake face and flank face of face milling cutter during processing time. Radial and axial throw of tooth were small and wear parameters are during processing time remain near for both cases. Tool wear of model single tooth and eight teeth face milling cutter were modeled by statistical method and artificial intelligence neural network model and were compared. Better models were achieved with artificial intelligence method.